Big Things for Big Cities (Oz, 1986)
Idea for Marconi Plaza. The symbolic purpose of this important urban project is to commemorate the Italian-American presence in Philadelphia and the contributions of this community to the City on the 500th Anniversary of Christopher Columbus' discovery of the New World...